Shallow implementation of quantum fingerprinting with application to quantum finite automata - Ziiatdinov, Mansur; Khadieva, Aliya; Khadiev, Kamil (Frontiers in Computer Science, 2025)
Quantum fingerprinting is a technique that maps a classical input word to a quantum state. The obtained quantum state is much shorter than the original word, and its processing uses fewer resources, making it useful in quantum algorithms, communication, and cryptography. One of the examples of quantum fingerprinting is the quantum automata algorithm for MODp={ai·p∣i≥0} languages, where p is a prime number. However, implementing such an automaton on current quantum hardware is not efficient. Quantum fingerprinting maps a word x∈{0, 1}n of length n to a state |ψ(x)〉 of O(logn) qubits, and uses O(n) unitary operations. Computing quantum fingerprint using all available qubits of the current quantum computers is infeasible due to many quantum operations. To make quantum fingerprinting practical, we should optimize the circuit for depth instead of width, in contrast to the previous works. We propose explicit methods of quantum fingerprinting based on tools from additive combinatorics, such as generalized arithmetic progressions (GAPs), and prove that these methods provide circuit depth comparable to a probabilistic method. We also compare our method to prior work on explicit quantum fingerprinting methods. We provide a series of numerical experiments with implementation of the quantum automata for MOD17 language on noisy simulators of IBMQ quantum devices. We show that shallow implementation based on GAPs produces results with much smaller computational error compared to standard deep circuit implementation. Despite the fact that on the ideal quantum computational device, the opposite situation arises. We show that the shallow circuit for the quantum automaton is better for near-future quantum computational devices.